2009
DOI: 10.1136/bjsm.2008.054841
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of developing the performance template

Abstract: Background: The pattern of energy expenditure during sustained high-intensity exercise is influenced by several variables. Data from athletic populations suggest that a pre-exercise conceptual model, or template, is a central variable relative to controlling energy expenditure. Aims: The aim of this study was to make systematic observations regarding how the performance template develops in fit individuals who have limited specific experience with sustained high-intensity exercise (eg, time trials). Methods: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
97
2
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(111 citation statements)
references
References 21 publications
11
97
2
1
Order By: Relevance
“…The current study therefore lends support to the existing literature suggesting that the pacing strategy adopted during self-paced exercise is anticipatory, based on the expectation of the exercise duration and other pertinent factors. 4,[27][28][29] It is astonishing that, given the many factors that could have influenced velocity over the duration of the event, similar lap pacing profiles were produced, resulting in the similar lap times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study therefore lends support to the existing literature suggesting that the pacing strategy adopted during self-paced exercise is anticipatory, based on the expectation of the exercise duration and other pertinent factors. 4,[27][28][29] It is astonishing that, given the many factors that could have influenced velocity over the duration of the event, similar lap pacing profiles were produced, resulting in the similar lap times.…”
Section: Discussionmentioning
confidence: 99%
“…While only 6 of the recruited participants competed in the race reported here, previous studies have clearly demonstrated the robustness of pacing. 27 In addition, since the data are reported over a 5-lap race (4 laps for women) they represent 29 individual laps in which high intralap variability has been observed. A second limitation is that power was not measured.…”
Section: Discussionmentioning
confidence: 99%
“…An associated component of self-efficacy is the confidence in being able to complete the exercise task required (7) without catastrophic failure before the end (23). Confidence maybe reinforced through repeated performances or experience; the memory of which, has been proposed to be one of the determinants of perceived exertion and effort regulation during a subsequent similar exercise task (51).…”
Section: Paragraph Number 23mentioning
confidence: 99%
“…Previous experience and knowledge of the exercise endpoint are essential factors in the formation of a stable performance template for a given exercise bout and the initial setting of work-rate (14,17), which is crucial in the development of an optimal pacing strategy. The mechanisms by which pacing strategy is continually regulated during exercise, however, have yet to be clearly identified (20,44), despite receiving considerable attention in the literature (1,8,32).…”
Section: Paragraph Numbermentioning
confidence: 99%